An effective freezing/thawing method for human pluripotent stem cells cultured in chemically-defined and feeder-free conditions - Nishishita, Naoki (Am J Stem Cells, 2015)
Culturing human Pluripotent Stem Cells (hPSC)s in chemically defined medium and feeder-free condition can facilitate metabolome and proteome analysis of culturing cells and medium, and reduce regulatory concerns for clinical application of cells. And in addition, if hPSC are passaged and cryopreserved in single cells it also facilitates quality control of cells at single cell level. Here we report a robust single cell freezing and thawing method of hPSCs cultured in chemically-defined medium TeSR(TM)-E8(TM) and on cost-effective recombinant human Vitronectin-N (rhVTN-N)-coated dish. Cells are dissociated into single cells with recombinant TrypLE(TM) Select and 0.5 mM EDTA/PBS (3:1 solution) in the presence of Rock inhibitor and cryopreserved with chemically defined CryoStem(TM). Approximately 60% of cells were viable after dissociation. Aggrewell(TM) 400 was used to form cell clumps of 500 cells after thaw in the presence of Rock inhibitor and cells were cultured for two days with TeSR-E8. Cells clumps were then seeded on rhVTN-N-coated dish and cultured with TeSR-E8 for two days prior to the first passage after thawing. Number of viable cells at the first passage increased around 10 times of that just before freezing. This robust single cell freezing method for hPSCs cultured in chemically defined medium will facilitate quality control of cultured cells at single cell level before cryopreservation and consequently assure the quality of cells in frozen vials for further manipulation after thawing.